2017
DOI: 10.1111/1745-9125.12133
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Street Network in Burglars' Spatial Decision‐making*

Abstract: That crime is spatially concentrated now seems incontestable (e.g., Eck and Weisburd, 1995). Explaining why this is so, however, is still a central theme of criminological research and a matter of some debate. Several prevailing theories assert that the environment plays a central role in shaping the distribution of crime by facilitating the convergence in space and time of offenders and suitable targets, in the absence of capable guardians (Cohen and Felson, 1979). One fundamental determinant of this is the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 55 publications
7
61
1
1
Order By: Relevance
“…Establishing a reduced burglary risk in properties along cul-de-sacs, Johnson and Bowers (2010) suggested that their reduced permeability might make cul-the-sacs unfamiliar places for non-residents, including most potential motivated offenders. Frith et al (2017) use the physical layout of the street network to generate alternative measures of offender spatial awareness, finding the reduced accessibility in the street network reduces the likelihood of street segments being targeted.…”
Section: Distance and Awareness Spacementioning
confidence: 99%
“…Establishing a reduced burglary risk in properties along cul-de-sacs, Johnson and Bowers (2010) suggested that their reduced permeability might make cul-the-sacs unfamiliar places for non-residents, including most potential motivated offenders. Frith et al (2017) use the physical layout of the street network to generate alternative measures of offender spatial awareness, finding the reduced accessibility in the street network reduces the likelihood of street segments being targeted.…”
Section: Distance and Awareness Spacementioning
confidence: 99%
“…Finally, recent extensions of OFT might prove to be valuable in the development of criminological theory, with some contemporary issues showing great similarity to issues in criminology. Criminological research into offender decision-making increasingly tries to account for between-offender differences, for example in the study of variation in journeys to crime (Townsley and Sidebottom, 2010;Van Daele, 2010) or in burglary location choice (Townsley et al, 2016;Frith et al, 2017). Similarly, studies in animal ecology are increasingly attentive to diet variation among members of the same species (e.g., Tinker et al, 2012;Bolnick et al, 2003;Cantor et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It could be that an increase in road network density is related to more ambient population, which would increase the risk of detection. Frith, Johnson [39] also argue that street networks are related to both levels of guardianship and accessibility and opportunities. In this research, it seems that road network density in residential burglars' home areas is more related to opportunities, whereas in target areas it seems more related to levels of guardianship.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The costs of travel are however not directly related to travel distance, because some places are better accessible than others, for example because they are better connected to the transportation system [37]. Several studies suggest that burglars would use the transportation system to travel over longer distances [38,39]. Vandeviver, Van Daele [7] used the rational choice perspective to understand why some offenders travel over long distances.…”
Section: Rational Choice Theory: Benefits Risks and Effortmentioning
confidence: 99%